POST-PROSTATECTOMY INCONTINENCE AND NURSING CARE: AN INTEGRATIVE REVIEW (Estima – Brazilian Journal of Enterostomal Therapy, 2022)
Objective: To identify nursing actions corresponding to assistance in post-prostatectomy urinary incontinence (PPUI). Method: This is an integrative review conducted in PubMed Central, ScienceDirect, Scopus and Web of Science, using the English terms “post-prostatectomy incontinence” and “nursing care,” combined with the Boolean operator AND. Articles published as full text or articles in press, within the open access system, without distinction of languages or year of publication, were included. Results: The initial search found 477 papers, but only six met the eligibility criteria. The five types of nursing actions identified were pelvic floor muscle training; urine stream interruption test with Unit Under Test timer; psychological nursing intervention program;telephone nursing support;and continuous post-prostatectomy nursing care, together with the previous interventions. Most studies showed good methodological quality and low risk of bias. Conclusion: The present review allowed the identification of different types of management of PPUI by nursing, even considering that the scenario of studies on the area is still scarce. It is expected that this review may be useful for the development of quality nursing care protocols for PPUI.